Age-Appropriate Pediatric Sports Patient-Reported Outcome Measures and Their Psychometric Properties: A Systematic Review. Issue 13 (November 2019) - Suryavanshi, Joash R.; Goto, Rie; Jivanelli, Bridget; ,; Aberdeen, Jamila; Duer, Timothy; Lam, Kenneth C.; Franklin, Corinna C.; MacDonald, James; Shea, Kevin G.; Fabricant, Peter D.
Background: Phenomena including early sport specialization and year-round training and competition have contributed to an increase in pediatric sports injuries. There has been a concomitant increase in clinical studies focusing on physically active children and adolescents. These studies include investigations of patient-reported outcome measures (PROMs). While the use of PROMs in pediatric orthopaedics has been increasing, PROMs are often inappropriately applied to study populations for whom they are not specifically validated. Purpose: The purpose of this study was to establish a comprehensive list of pediatric- and adolescent-validated PROMs and catalog their psychometric properties as a resource for clinicians and researchers. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review of articles in PubMed, Embase, and the Cochrane library was performed to identify articles developing and validating PROMs appropriate for use in pediatric sports medicine research. The inclusion criteria were as follows: age <18 years, the use of surveys and questionnaires, and the presence of sports-related injuries. The psychometric properties of included PROMs were entered into an electronic database. Results: Our search strategy identified 14, 708 unique articles, among which 139 studies (0.9%) were included in the final data analysis. Forty-seven distinct PROMs were identified, as well as 160 cross-cultural adaptations. While all identified PROMs were validated in physically active young participants, only 12 (26%) were specifically created initially for active children. Thirty (64%) PROMs were health-related quality-of-life measures; 13 (28%) were psychosocial measures; and 4 (9%) were activity scales. No studies validated PROMs for use with wrist/hand injuries, and only 1 PROM each was valid for hip, back/spinal, and foot/ankle injuries in pediatric sports. Conclusion: This systematic review yielded 47 unique PROMs reliable and valid for use in pediatric and adolescent sports medicine. This list will unify clinicians and researchers in using these age-appropriate measures while identifying areas that are still in need of appropriate PROMs for young athletes.